2016
DOI: 10.1177/2381336916661535
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Eye Movements, Miscue Analysis Patterns, and Retellings When Reading a Counterpoint Picture Book

Abstract: This study incorporated eye movement miscue analysis to investigate two secondgraders' oral reading and comprehension of a counterpoint picture book. Findings suggest the second-graders' strategies when reading the written and pictorial text affected their comprehension as opposed to the number and location of their eye movements. Specifically, the data highlight the contextual nature of the counterpoint picture book and how the readers' strategies influenced the ways students navigated the text, what they fix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Literacy researchers have engaged in a variety of approaches to study reading by focusing on how the affordances of picture books influence reading strategies and comprehension (Feathers & Arya, 2015; Liwanag, Pelatti, Martens, & Martens, 2016). Researchers conducting these studies found that readers’ gaze or attention to the written and pictorial information in different kinds of picture books influence readers’ understanding of the materials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Literacy researchers have engaged in a variety of approaches to study reading by focusing on how the affordances of picture books influence reading strategies and comprehension (Feathers & Arya, 2015; Liwanag, Pelatti, Martens, & Martens, 2016). Researchers conducting these studies found that readers’ gaze or attention to the written and pictorial information in different kinds of picture books influence readers’ understanding of the materials.…”
mentioning
confidence: 99%
“…Our recent EMMA study (Liwanag et al, 2016) and other ongoing EMMA research have shown that common metrics (Goodman, 2016) do not fit the traditional definition of a fixation that lasts between 200 and 300 ms (Holmqvist et al, 2015) as the “only time the eye transmits useable data to the brain” (Paulson & Freeman, 2003, p. 2). While we recognize the value of fixations as a measure of cognitive processing, we are in need of a new method that considers other metrics, such as gaze points, to explain how visual input from the eyes is used to make sense when reading.…”
mentioning
confidence: 99%